2021
DOI: 10.3389/fcell.2021.707938
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Disease-Related 2-Oxoglutarate/Fe (II)-Dependent Oxygenase Based on Reduced Amino Acid Cluster Strategy

Abstract: The 2-oxoglutarate/Fe (II)-dependent (2OG) oxygenase superfamily is mainly responsible for protein modification, nucleic acid repair and/or modification, and fatty acid metabolism and plays important roles in cancer, cardiovascular disease, and other diseases. They are likely to become new targets for the treatment of cancer and other diseases, so the accurate identification of 2OG oxygenases is of great significance. Many computational methods have been proposed to predict functional proteins to compensate fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 66 publications
1
3
0
Order By: Relevance
“…Our results are consistent with previous studies that showed 2OG‐Fe (II) oxygenases are involved in various aspects of plant development in O. sativa and A. thaliana , especially flowering (Low et al., 2020; Steinbauer et al., 2018; Zhou et al., 2021). A recent study on barley revealed that a 2OG‐Fe (II) oxygenase gene ( HvDMR6 ) is a functional ortholog of A. thaliana DMR6 , which is required for floral organ development (Low et al., 2020).…”
Section: Resultssupporting
confidence: 93%
“…Our results are consistent with previous studies that showed 2OG‐Fe (II) oxygenases are involved in various aspects of plant development in O. sativa and A. thaliana , especially flowering (Low et al., 2020; Steinbauer et al., 2018; Zhou et al., 2021). A recent study on barley revealed that a 2OG‐Fe (II) oxygenase gene ( HvDMR6 ) is a functional ortholog of A. thaliana DMR6 , which is required for floral organ development (Low et al., 2020).…”
Section: Resultssupporting
confidence: 93%
“…In recent years, we successively constructed iDEF-PseRAAC, RaacLogo, RaacBook, OGFE-RAAC and other protein analysis and prediction platforms based on RAA alphabets, which enriched the application scope of RAA alphabets and emphasized the important role of simplified amino acid composition in sequence-structure–function ( Fig. 1 D and Table 1 ) [12] , [13] , [14] , [15] , [59] .…”
Section: The Classification Of Protein Function Based On Reduced Amin...mentioning
confidence: 99%
“…The simplified amino acid composition greatly reduces the dimensions of traditional feature engineering, effectively suppresses the negative effects of noise, and provides the model with richer biological prior knowledge to extract key features [12] , [13] . In addition, it is highly inclusive and has good compatibility with many existing methods, which helps to promote the further integration of traditional machine learning and biology [14] , [15] .…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of genes encoding these two proteins suggests that they may play a vital role in these phages; however, their specific functions remain to be explored. The 2OG-Fe(II) oxygenase superfamily is typically involved in the oxidation of organic substrate using a dioxygen molecule, which is mainly responsible for protein modification, nucleic acid repair and/or modification, and fatty acid metabolism ( 60 , 61 ). Fe-S cluster participates in a wide variety of cellular biological processes ( 62 ).…”
Section: Discussionmentioning
confidence: 99%